Toward wide-scale all-optical transparent networking the ACTS optical pan-European network (OPEN) project. - Chbat, M.W.
The European ACTS project optical pan-European network (OPEN) aims at assessing the feasibility of an optical pan-European overlay network, interconnecting major European cities by means of a mesh of high-capacity optical fiber links, cross-connected through transparent photonic nodes. Both the transmission links and the routing network elements rely on wavelength division multiplexing (WDM) all-optical technologies, such as wavelength translation. This paper presents results obtained in the following domains covered within the project: network topology considerations (optimization and dimensioning); network physical layer simulation; fabrications of packaged functional modules based on advanced optoelectronic devices; laboratory demonstrations of N×10 Gb/s transmission and routing; feasibility of an optical time division multiplexing/WDM (OTDM/WDM) interface; and the field implementation of a 4×4 multiwavelength crossconnect prototype, featuring all-optical space and wavelength routing. This implementation was realized in two cross-border field trials, one conducted between Norway and Denmark and the other between France and Belgium. The final results of the Norway to Denmark field trials are presented, featuring the successful cascade of three wavelength-translating optical crossconnects (OXCs), along with the transmission over 1000 km of a mix of standard/submarine cable links for four channels at 2.5 Gb/s
Keywords: 10 Gbit/s.; 1000 km; 2.5 Gbit/s.; ACTS optical pan-European network; Belgium; Denmark; France; Norway; OPEN project; OTDM/WDM interface; WDM all-optical technologies; All-optical space routing; Dimensioning; High-capacity optical fiber links; Laboratory demonstrations; Multiwavelength crossconnect prototype; Network physical layer simulation; Network topology; Optical crossconnects; Optical pan-European overlay network; Optical time division multiplexing; Optimization; Optoelectronic devices; Packaged functional modules; Routing network elements; Standard/submarine cable links; Transparent photonic nodes; Wavelength division multiplexing; Wavelength routing; Wavelength translation; Wide-scale all-optical transparent networking